2017
DOI: 10.1002/hep.29089
|View full text |Cite
|
Sign up to set email alerts
|

The human longevity gene homolog INDY and interleukin‐6 interact in hepatic lipid metabolism

Abstract: Reduced expression of the Indy (‘I am Not Dead, Yet’) gene in lower organisms promotes longevity in a manner akin to caloric restriction. Deletion of the mammalian homolog of Indy (mIndy, Slc13a5) encoding for a plasma membrane associated citrate transporter expressed highly in the liver, protects mice from high-fat diet and aging-induced obesity and hepatic fat accumulation through a mechanism resembling caloric restriction. We aimed to study a possible role of mIndy in human hepatic fat metabolism. In obese,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 51 publications
2
84
0
2
Order By: Relevance
“…We identified the positional candidate gene Slc13a5 (S3H Fig), which is a sodium-dependent transporter that mediates cellular uptake of citrate, an important precursor in the biosynthesis of fatty acids and cholesterol (54). Recent evidence indicates that Slc13a5 influences host metabolism and energy homeostasis (5557). Slc13a5 is a transcriptional target of pregnane X receptor (PXR) (58), which also regulates the expression of genes involved in the biosynthesis, transport, and metabolism of BAs (59).…”
Section: Resultsmentioning
confidence: 99%
“…We identified the positional candidate gene Slc13a5 (S3H Fig), which is a sodium-dependent transporter that mediates cellular uptake of citrate, an important precursor in the biosynthesis of fatty acids and cholesterol (54). Recent evidence indicates that Slc13a5 influences host metabolism and energy homeostasis (5557). Slc13a5 is a transcriptional target of pregnane X receptor (PXR) (58), which also regulates the expression of genes involved in the biosynthesis, transport, and metabolism of BAs (59).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates an improvement in glucose tolerance in KD-64-treated mice compared to the obese control mice which might be connected to the anti-inflammatory effect of the tested compound and a decrease in plasma IL-6 levels, since IL-6 and its signalling path play complex roles in metabolic disorders [72]. It was recently reported that IL-6 enhances fatty acid synthesis in murine hepatocytes via the induction of the citrate transporter mIndy [73] and it also exacerbates hepatic inflammation and steatosis [74]. Additionally, adenosine has been shown to promote IL-6 production [75] and our study demonstrates that adenosine A 2A receptor may be associated with this activity, because selective antagonist of this particular receptor decreased IL-6 level in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…(1) We were well aware of the difference in the definition of hepatitis B virus (HBV) reactivation (HBVr) across the studies. However, due to the limited data reported in the included studies, we were unable to use a standardized definition, HBV replication 2 log increase from baseline levels, or a new appearance of HBV DNA to a level of 100 IU/mL (2) to adjust the pooled results.…”
Section: Replymentioning
confidence: 99%